2010
DOI: 10.1016/j.jtcvs.2010.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Increased age is an independent risk factor for radiographic aspiration and laryngeal penetration after thoracotomy for pulmonary resection

Abstract: Postoperative risk of aspiration after thoracotomy for pulmonary resection is characterized by repeatable episodes of oropharyngeal discoordination on videofluoroscopic swallowing studies. We recommend routine videofluoroscopic swallowing studies for all patients older than 67 years before the initiation of oral intake to diminish the incidence of postoperative aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…Furthermore, we demonstrated that these patients had a risk of respiratory morbidity and 90‐day mortality. Although it was not the objective of the study, older age was not significantly associated with a higher rate of swallowing disorders, contrary to what had been reported on by Keeling et al . This may be explained by the relatively small number of patients with aspiration in our study.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we demonstrated that these patients had a risk of respiratory morbidity and 90‐day mortality. Although it was not the objective of the study, older age was not significantly associated with a higher rate of swallowing disorders, contrary to what had been reported on by Keeling et al . This may be explained by the relatively small number of patients with aspiration in our study.…”
Section: Discussioncontrasting
confidence: 88%
“…estimated the incidence of aspiration at 17.8% following pulmonary resection, based on clinical history enhanced with dynamic videofluoroscopic esophagramography . The authors also described the importance of older age in the development of post‐operative aspiration, recommending the routine use of videofluoroscopic swallowing studies for all patients older than 67 years, before post‐operative food intake . In our study, aspiration was assessed at the bedside using a blue‐coloured water test and endoscopic assessment for all patients, symptomatic or not, allowing us to diagnose 18 of 250 patients (7.2%) with swallowing disorders, which is lower than in the Keeling et al .’s study .…”
Section: Discussionmentioning
confidence: 94%
“…Dysphagia is a common consequence of disease and aging, is associated with complications in pneumonia, and has a particularly high mortality and morbidity in older adults. [1][2][3][4][5] The bedside water swallowing test is commonly used for clinical evaluation of swallowing function, but is not sensitive enough to detect small age-related alterations in swallowing. [6][7][8][9] Recent studies have documented both the neurophysiological and clinical significance of the coordination of respiration with swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia is well known to occur as a complication of intrathoracic surgical procedures [1][2][3][4][5][6][7][8]. There are numerous reports of the investigation of postoperative dysphagia after cardiac operations [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%